2005
DOI: 10.1002/smll.200400137
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Aligned Carbon Nanotube–Ruthenium Oxide Nanocomposites for Supercapacitors

Abstract: A novel type of ruthenium oxide (RuO(2))-modified multi-walled carbon nanotube (MWNT) nanocomposite electrode (RuO(2)/MWNT) for supercapacitors has been prepared. The nanocomposites were formed by depositing Ru by magnetic-sputtering in an Ar/O(2) atmosphere onto MWNTs, which were synthesized on Ta plates by chemical vapor deposition. Cyclic voltammetry, chronopotentiometry, and electrochemical impedance measurements were applied to investigate the performance of the RuO(2)/MWNT nanocomposite electrodes. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(112 citation statements)
references
References 36 publications
2
107
1
2
Order By: Relevance
“…Figure 4(d) illustrates the results of impedance spectroscopy on a bare SWNT thin film and a hybrid RuO 2 nanowire/SWNT nanostructured thin film in 0.3 mol/L H 2 SO 4 solution, at a dc bias voltage of 0.1 V, with a 10 mV amplitude sinusoidal signal and a wetted area of 0.5 cm 2 . In contrast to the bare SWNT thin film electrode, the Nyquist plot of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode shows that the imaginary part of impedance increases sharply at lower frequency, which indicates that SWNT films retain their electron-transfer capability even with the integration of RuO 2 nanowires [39]. It can be seen that the diameters of the semicircle in the Nyquist plot of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode is smaller than that of the bare SWNT thin film electrode, which means that the electrochemical reactions on the electrode/electrolyte interface of hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode are more facile than on the bare SWNT thin film electrode [40].…”
Section: Resultsmentioning
confidence: 89%
“…Figure 4(d) illustrates the results of impedance spectroscopy on a bare SWNT thin film and a hybrid RuO 2 nanowire/SWNT nanostructured thin film in 0.3 mol/L H 2 SO 4 solution, at a dc bias voltage of 0.1 V, with a 10 mV amplitude sinusoidal signal and a wetted area of 0.5 cm 2 . In contrast to the bare SWNT thin film electrode, the Nyquist plot of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode shows that the imaginary part of impedance increases sharply at lower frequency, which indicates that SWNT films retain their electron-transfer capability even with the integration of RuO 2 nanowires [39]. It can be seen that the diameters of the semicircle in the Nyquist plot of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode is smaller than that of the bare SWNT thin film electrode, which means that the electrochemical reactions on the electrode/electrolyte interface of hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode are more facile than on the bare SWNT thin film electrode [40].…”
Section: Resultsmentioning
confidence: 89%
“…Depending on the reaction temperature, the Zn particles reacted with oxygen impurities in argon to form a coating on the CNTs consisting either of spherical particles (450 °C), nanowires (800 °C), or short nanorods (900 °C). RF or magnetron sputtering has been used to deposit RuOx, [194] and ZnO [195]. Furthermore, Jin et al have cosputtered Ba and Sr in an oxygen atmosphere to obtain a BaO/SrO coating [196].…”
Section: Evaporation and Sputteringmentioning
confidence: 99%
“…the electrochemical stability of transition metal oxides makes them a better choice, provided they are highly conducting. A wide range of oxides has been investigated for use in CNT hybrids, including NiO [171,232,233], MnO 2 [234][235][236][237], V 2 O 5 [238,239], and RuO 2 [169,192,194]. In all of these studies, the synergistic effects of CNT oxide hybrids have shown a considerable improvement of the otherwise poor electric properties and deficient charge transfer channels of the pure oxide.…”
Section: Supercapacitors and Batteriesmentioning
confidence: 99%
“…The development of various carbonaceous electrode materials for supercapacitors has been an important issue in view of their large specific surface, controlled pore structure, ability to adjust the ratio of micropores to mesopores, good conductivity, and functionalization of the materials [16][17][18][19]. Carbon materials with large specific surface areas due to the presence of micropores exhibit a high capacitance and are known to selectively accommodate effective charge carriers, including the solvation shell of the ions [20].…”
Section: Introduction 1)mentioning
confidence: 99%